Restauración urbana – integral de los humedales objeto de estudio: humedal juan amarillo (2019)
This project is proposed in the Juan Amarillo Wetland, located in the city of Bogotá, towards the northwest between the towns of Suba and Engativá. Due to urban densification, it has suffered from a series of alterations in round areas, generating problems of acoustic, atmospheric and aquifer pollution.